Absence of renal adverse effects from β-myrcene dietary administration in OECD guideline-compliant subchronic toxicity study. (October 2018) - Bastaki, Maria; Aubanel, Michel; Bauter, Mark; Cachet, Thierry; Demyttenaere, Jan; Diop, Maodo Malick; Harman, Christie L.; Hayashi, Shim-mo; Krammer, Gerhard; Li, Xiaodong; Llewellyn, Craig; Mendes, Odete; et al.
Abstract: β-Myrcene is a flavoring substance that occurs naturally in a large variety of foods. At the request of the European Food Safety Authority (EFSA) for additional toxicological data on β-myrcene, groups of Sprague Dawley rats (10/sex/group) were administered diets containing 0, 700, 2100, or 4200 ppm of β-myrcene designed to provide nominal doses of 0, 50, 150, or 300 mg/kg bw/day in a 90-day GLP-compliant study. Based on body weights, feed consumption, and substance stability data, final estimated daily intakes of β-myrcene were calculated to be 20.4, 58.8, and 115.2 mg/kg bw for males and 24.2, 70.0, and 135.9 mg/kg bw for females. No effects on clinical observations, hematology and clinical chemistry parameters, organ weights, or macroscopic and histopathological examinations were found attributable to ingestion of β-myrcene. The oral no-observed-adverse-effect level (NOAEL) for rats of both sexes was the highest dose tested. Based on feed consumption and test substance stability in the diet, the NOAEL was calculated to be 115 and 136 mg/kg bw/day for males and females, respectively. Highlights: GLP-compliant 90-day study following OECD guideline on β -myrcene. A threshold of toxicity (NOAEL) of 115 and 136 mg/kg bw/day in males and females is proposed for β-myrcene.